The negotiation of educational opportunity: the final years of compulsory schooling in a multi-ethnic inner-city comprehensive - Gillborn, David (1987)
This thesis reports a case study of the final years of compulsory schooling in a multi-ethnic inner-city school (City Road Comprehensive). Data was collected during two years of intensive ethnographic field work, principally via informal interviews and participant observation. Pupils in two mixed ability form groups were studied as they moved through the subject options process of the third year, throughout their fourth year and into the final year of compulsory education. A third mixed ability form group were also studied during the subject options process. The thesis explores some of the school-based influences which shaped the pupils' experience of City Road. Following a consideration of my research methodology, and a brief description of the social composition and academic organization of the school, Chapters 2, 3 and 4 offer a detailed -analysis of the subject options process. Although the pupils' gained access to a majority of their original option choices, it was the senior staff who came to dominate the options system. However, form tutors and subject teachers also retained some influence over pupils' decisions. The options process represented a form of academic selection, resulting in significant differences between pupils' upper school curricula. Gender and the senior staff's perception of pupils' 'ability' were particularly important. Chapters 5 and 6 turn to the pupils' experience of the upper school. In a modified form the processes of differentiation and polarization, described in previous case studies (Hargreaves, 1967; Lacey, 1970; Ball, 1981), were seen to operate within City Road. The complex, negotiated character of pupil adaptations is examined, analysing the factors in the teacher-pupil relationship which placed West Indian pupils in a relatively disadvantaged position within the pupil population. I conclude by considering aspects of the 'micro-macro' problem and highlighting the need for further research arising from this study.